Data visualisation with a simple syntax - Hedström, Jimmy; Hult, John; Göthe, Patrik; Nilsson, Oscar; Alaraj, Morhaf; Nääs, David (My University, 2015)
This thesis describes the development of Marker, a syntax based data visualisation platform with the power and flexibility of a programmers tool, but usable by anyone, programmer or not. Today more open data than ever is available thanks to the internet but few people have access to the means to use it. Consequently, some actors on the internet have the ability to analyse and draw conclusions from data while some do not. Marker’s purpose is to bridge the gap that this creates. The project was divided in two parts, a pre-study and the actual development of the application. The pre-study was conducted as a literature study and in the form of interviews with experts on the area of data visualisation. The development was documented in the form of system design decisions and a full description of the end result. Based on the results, Marker’s usefulness and viability in comparison to similar tools and its intended purpose is discussed. The conclusion was made that Marker’s usability and extendable system design adds new value to the area of data visualisation. However, more development and user testing is required in order to make Marker a competitive alternative to the existing data visualisation tools of today.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science